THE ROLE OF RELIGIOUS-BASED BEHAVIORAL COUNSELING IN CHANGING STUDENTS DELINQUENCY - Hera Heru Sri Suryanti Sri Hartini (RESEARCH FAIR UNISRI, 2018)
Students who experiencing delinquency in the scope of Higher Education should beimmediately assisted because it disrupts their development. If the development isdisrupted then the low performance index that ultimately can not be prepared to be ascholar candidate who is reliable.For that reason, they need to be given the rightcounseling that can change the delinquency to be adaptive.One of the most appropriatecounseling is religious-based Behavioral counseling. This study aims to: to illustrate theimplementation of religious-based Behavioral Counseling Model in dealing with studentsexperiencing delinquency to be an adaptive student. The method used in this research isdescriptive qualitative research continued with Counseling Guidance Action Research.The research was conducted at FKIP UNISRI Surakarta. Study time is planned for 6months. Beginning with the data collection of students who experienced delinquency thencontinued with the application of behavioral counseling based on the student's religious.Population in this research is student of FKIP UNISRI, Sample in this research is studentof study program. Techniques Data collection using interviews, observation, FGD, andTests (questionnaire), while the validity of the data using source triangulation,triangulation method, and Member checking. Analysis of data used is an interactiveanalysis model as proposed by Miles and Huberman (1992). The results showed thatreligious-based counseling can change the delinquency students into adaptive students.Key words: religious-based Behavioral counseling, delinguency, students